2023
DOI: 10.1186/s12870-023-04233-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analyses and phylogenetic relationships of thirteen Pholidota species (Orchidaceae) inferred from complete chloroplast genomes

Abstract: Background The orchid genus Pholidota Lindl. ex Hook. is economically important as some species has long been used in traditional medicine. However, the systematic status of the genus and intergeneric relationships inferred from previous molecular studies are unclear due to insufficient sampling and lack of informative sites. So far, only limited genomic information has been available. The taxonomy of Pholidota remains unresolved and somewhat controversial. In this study, the complete chloropla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
(65 reference statements)
0
3
0
Order By: Relevance
“…These GC values fall within the limit of variation registered in others studies 24,60 . Furthermore, a study about several orchid species, showed that the species with a smallest chloroplast size (Pholidota cantonensis, 158,786 bp), had a highest GC content (37.47%) 61 , similar to our observations. The plastid genome tends to reduce its size during evolution 62 , and gene length might be affected by selection during the evolution of spermatophytes 63 .…”
Section: Discussionsupporting
confidence: 90%
“…These GC values fall within the limit of variation registered in others studies 24,60 . Furthermore, a study about several orchid species, showed that the species with a smallest chloroplast size (Pholidota cantonensis, 158,786 bp), had a highest GC content (37.47%) 61 , similar to our observations. The plastid genome tends to reduce its size during evolution 62 , and gene length might be affected by selection during the evolution of spermatophytes 63 .…”
Section: Discussionsupporting
confidence: 90%
“…For example, the 3 end of the rpl22 gene of all six species of Aerides, which should be intact in the LSC region, extended into the IRb region for 30-31 bp, which was found in Renanthera [22]. In addition, the ycf1 gene in the SSC region of other orchids (such as Pholidota [23] and Thuniopsis [24]) was observed crossing over JSA, extending into the IRa region. However, the ycf1 of Aerides was intact in the SSC region.…”
Section: The Plastome Characteristics and Structural Evolutionmentioning
confidence: 98%
“…Some researchers have used the cp genome to mine mutation sites to distinguish closely related species (especially some weed relatives), or have used the cp genome to elaborate new perspectives on plant phylogenetic relationships and taxonomy. The importance and efficiency of chloroplast genomes in related research have been confirmed by more and more studies [40,41].…”
Section: Introductionmentioning
confidence: 83%